Low-dose sublingual immunotherapy compared to subcutaneous immunotherapy and conventional therapy in childhood asthma - Ariyanto Harsono (Paediatrica Indonesiana, 2004)
Background Evidence begin to accumulate that high-dose sub-lingual immunotherapy (SLIT) is as effective as subcutaneousimmunotherapy (SIT) in the treatment of childhood asthma.Since the capacity of sublingual area is similar whether the doseis high or low, the efficacy of low dose may be important to bestudied.Objective To investigate the efficacy of low-dose sublingual im-munotherapy in the treatment of childhood asthma.Methods Parents signed informed consent prior to enrollment,after having received information about the study. Patients weremoderate asthma aged 6-14 years with disease onset of lessthan 2 years before the commencement of the study and peakexpiratory flow rate (PEFR) variability of more than 15%. Pa-tients were randomly allocated into group A, B, and C whoreceived subcutaneous immunotherapy, low-dose sublingualimmunotherapy, and conventional asthma therapy, respectively.Randomization was stratified into two strata according to agei.e., 6-11 years or 11-14 years. Patients of each stratum wererandomized in block of three for each group. At the end of threemonths, lung function tests were repeated. The primary outcomewas PEFR variability at the end of the study. The study wasapproved by the Ethics Committee of Soetomo HospitalSurabaya.Results Distribution of variants as represented by sex, age,eosinophil count, and total IgE concentration were normal inthe three groups. PEFR variability decreased significantly from16.97+0.81 to 8.50+5.08 and 17.0+0.87 to 8.40+4.72 in groupreceiving SIT and SLIT, respectively (p<0.05), but decreasednot significantly from 17.00+0.83 to 10.82+0.5.41 in control group(p>0.05).Conclusion Low-dose SLIT is as efficacious as SIT in the treat-ment of moderate asthma in children